2018
DOI: 10.1038/s41437-018-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of subdioecy and scarcity of gender-specific markers reveal an ongoing transition to dioecy in Himalayan seabuckthorn (Hippophae rhamnoides ssp. turkestanica)

Abstract: Dioecy and the dynamics of its evolution are intensely investigated aspects of plant reproduction. Seabuckthorn (Hippophae rhamnoides ssp. turkestanica) is an alpine shrub growing wild in certain parts of western Himalaya. The previous studies have reported heteromorphic sex chromosomes in the species and yet marker-based studies indicate high similarity between the male and female genomes. Lack of information on sexual system in the species has further complicated the situation. A systematic study was thus un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, we did not find any habitat-influenced bias in such traits of Seabuckthorn. These findings reiterate our previous conclusions of having limited differences between the genomes of sexes in the species, and of the ongoing evolution of dioecy in Seabuckthorn [ 51 ]. Thus, it is likely that sexual dimorphism in the species has recently evolved or ongoing in the species at the site.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we did not find any habitat-influenced bias in such traits of Seabuckthorn. These findings reiterate our previous conclusions of having limited differences between the genomes of sexes in the species, and of the ongoing evolution of dioecy in Seabuckthorn [ 51 ]. Thus, it is likely that sexual dimorphism in the species has recently evolved or ongoing in the species at the site.…”
Section: Discussionsupporting
confidence: 89%
“…rhamnoides the authors have suggested that 2800 m altitude represents the range for optimal growth of H . rhamnoides ; at higher altitudes water stress induces negative impact on females through poor growth and greater mortality [ 51 ]. Thus, it is likely that the biased sex-ratio may be associated with changing altitude, with SK at the higher elevation (≥300 m), which also conforms with findings in Rumex nivalis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 25 wild populations of H. rhamnoides subsp. turkestanica in northern India showed that 2-4% of the plants were polygamomonoecious (PGM) with male, female, and hermaphrodite flowers, suggesting that the transition from hermaphrodites (the original state for angiosperms) to dioecy (the derived state) happened recently in this genus [38]. Moreover, the male and female genomes appear to be very similar overall.…”
Section: Sex Determinationmentioning
confidence: 99%
“…A Representational Difference Analysis (RDA) of DNA sequences was applied to the search for gender-specific differences between male and female genomes. Some of the obtained polymorphisms looked promising initially, but none of them held up when screened on plants from more distant populations [38].…”
Section: Sex Determinationmentioning
confidence: 99%
See 1 more Smart Citation